Water Structure in the Submembrane Region of a Floating Lipid Bilayer The Effect of an Ion Channel Formation and the Channel Blocker - Su, ZhangFei (Langmuir : the ACS journal of surfaces and colloids, 2020)
The structure of water in the submembrane region of the bilayer of DPhPC floating (fBLM) on a monolayer of 1-thio-β-d-glucose (β-Tg)-modified gold nanoparticle film was studied by the surface-enhanced infrared absorption spectroscopy (SEIRAS). SEIRAS employs surface enhancement of the mean square electric field of the photon, which is acting on a few molecular layers above the film of gold nanoparticles. Therefore, it is uniquely suited to probe water molecules in the submembrane region and provides unique information concerning the structure of the hydrogen bond network of water surrounding the lipid bilayer. The IR spectra indicated that water with a strong hydrogen network is separating the membrane from the gold surface. This water is more ordered than the water in the bulk. When alamethicin, a peptide forming ion channels, is inserted into the membrane, the network is only slightly loosened. The addition of amiloride, an ion channel blocker, results in a significant decrease in the amount of water in the submembrane region. The remaining water has a significantly distorted hydrogen bond network. This study provides unique information about the effect of the ion channel on water transport across the bilayer. The electrode potential has a relatively small effect on water structure in the submembrane region. However, the IR studies demonstrated that water is less ordered at positive transmembrane potentials. The present results provide significant insight into the nature of hydration of a floating lipid bilayer on the gold electrode surface